Large-scale analysis of the regulatory architecture of the mouse genome with a transposon-associated sensor - Ruf, Sandra; Dolle, Dirk-Dominik; Ettwiller, Laurence (Nature genetics, 2011)
We present here a Sleeping Beauty-based transposition system that offers a simple and efficient way to investigate the regulatory architecture of mammalian chromosomes in vivo. With this system, we generated several hundred mice and embryos, each with a regulatory sensor inserted at a random genomic position. This large sampling of the genome revealed the widespread presence of long-range regulatory activities along chromosomes, forming overlapping blocks with distinct tissue-specific expression potentials. The presence of tissue-restricted regulatory activities around genes with widespread expression patterns challenges the gene-centric view of genome regulation and suggests that most genes are modulated in a tissue-specific manner. The local hopping property of Sleeping Beauty provides a dynamic approach to map these regulatory domains at high resolution and, combined with Cre-mediated recombination, allows for the determination of their functions by engineering mice with specific chromosomal rearrangements.
Gesehen am 17.05.2017